Adoption of Investment Game Application (IGA) for digital product profiling for rice breeding by NARES partners - CGIAR Research Program on Rice (2019)
An R&D License Agreement (021216) for the use of the Investment Game Application (IGA) has been signed between IRRI and BRRI on 5 December 2016. The Bangladesh Rice Research Institute (BRRI) is currently using the IGA in product profiling. An R&D License Agreement will be prepared for the Cambodian Agricultural Research and Development Institute (CARDI).